Paul spent $6 on the student discount card. 23 times 1.60 equals 36.80. Subtract that from 42.80 and you get 6
Answer:
FG
Step-by-step explanation:
Answer:
(x+1)(x-1)(x+3)(x-3)
Step-by-step explanation:
x4-10x^2+9
Group expression so that the coefficients of the x^2 terms add up to +9.
= x^4 -9x^2 - x^2+9
match coefficients in both groups
= x^4 -9x^2 - (x^2-9)
factor each group
= x^2 (x^2-9) - 1(x^2-9)
now factor out the common factor (x^2-9)
= (x^2-1)(x^2-9)
Finally, factor each quadratic factor
= (x+1)(x-1)(x+3)(x-3)
C is the answer hope this helps.